Análisis de los patrones de comunicación en la familia de origen de las adolescentes embarazadas entre 13 y 18 años de la sala "A" del Hospital Gineco Obstétrico Isidro Ayora. - Vaca Yépez, Paola Alejandra (2012)
The following research entitled "Analysis of communication patterns in the family of origin of pregnant adolescents between 18 and 18 years of Room A of Obstetrics and Gynecology Hospital Isidro Ayora" constitutes a psychological analysis with a systems approach which analyzes communication styles that adopts the family of origin are travesando adolescents for pregnancy, because this event brings a combined crisis.